A highly efficient and simple lithium carbonate solution crystallization assembly and method
Patent Information
- Application Number
- CN202411038020.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-07-31
AI Technical Summary
[0004]本发明的目的在于,针对上述不足之处提供一种高效简易的碳酸锂溶液结晶组件和方法,解决了现有技术中在实验室制备碳酸锂晶体时晶体体积小,结晶过程复杂的问题
[0022]1、本方案在使用本组件时,首先在容器中配置好饱和碳酸锂溶液,然后将配置好的溶液放置到冷冻组件中进行冷冻处理,使溶液温度降低,有利于后续结晶,然后将冷冻后的饱和溶液进行过滤,过滤出不能溶解的碳酸锂粉末,然后通过泵体将液体排放到结晶组件中,通过纤维的方式进行结晶,与传统的结晶方式相比,能够凝结出更大颗粒的晶体,最后通过泵体将结晶组件中的废液进行排离。
Smart Images

Figure CN119113560B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium carbonate solution crystallization, and particularly to a highly efficient and simple lithium carbonate solution crystallization assembly and method. Background Technology
[0002] Lithium carbonate has a wide range of applications. As a core raw material in the lithium battery industry, its main current use is in the preparation of lithium battery cathode materials for use in new energy vehicles and energy storage. The end-use of lithium carbonate mainly involves industrial-grade and battery-grade applications. Battery-grade lithium carbonate is ultimately used in downstream consumer electronics industries, with new energy batteries being the primary application. Industrial-grade lithium carbonate can be used in lubricants, catalysts, traditional ceramics, glass, and other industries. It can also be purified to obtain battery-grade lithium carbonate for use in the new energy industry.
[0003] The raw material for producing crystalline lithium carbonate in the laboratory is lithium carbonate powder with a high concentration, which is then subjected to crystallization experiments. The crystals obtained by conventional crystallization methods in the present technology are small in size and cannot meet the requirements of the present technology. Summary of the Invention
[0004] The purpose of this invention is to provide an efficient and simple lithium carbonate solution crystallization assembly and method to address the above-mentioned shortcomings, thereby solving the problems of small crystal volume and complex crystallization process in the laboratory preparation of lithium carbonate crystals in the prior art.
[0005] This invention is achieved through the following scheme:
[0006] A high-efficiency and simple lithium carbonate solution crystallization assembly includes, but is not limited to, a freezing assembly, a filtration assembly, a crystallization assembly, and a drainage assembly; the freezing unit is used to freeze the prepared solution, the filtration assembly is used to filter the frozen solution, the crystallization assembly is used to crystallize the filtered solution, and the drainage assembly is used to drain the waste liquid from the crystallization assembly; the crystallization assembly is provided with fibers for crystallization, and the filtration assembly and the drainage assembly are connected to the crystallization assembly via a pump.
[0007] Based on the above-mentioned structure of a high-efficiency and simple lithium carbonate solution crystallization assembly, the freezing assembly is a freezing box, and the filtration assembly consists of a glass rod, filter paper, and a funnel; the filter paper is placed on the funnel, and the lithium carbonate solution is guided onto the filter paper for filtration by the glass rod; the filtration assembly and the drainage assembly are respectively connected to the crystallization assembly via peristaltic pumps.
[0008] Based on the above-mentioned structure of a high-efficiency and simple lithium carbonate solution crystallization component, the crystallization component includes a crystallizer, a cover, a glass carrier, and fiber filaments; the fiber filaments are disposed on the glass carrier, the crystallizer has an opening at its upper end, the cover is placed on the crystallizer, and the cover has vent holes.
[0009] Based on the above-mentioned structure of a high-efficiency and simple lithium carbonate solution crystallization component, the crystallization component includes a crystallizer, a cover, a crystallization frame, tree-shaped parallel fine glass components, and fiber filaments; the crystallizer has an opening at the upper end, the cover has a vent hole, the cover is placed on the crystallizer, multiple tree-shaped parallel fine glass components are arranged on the crystallization frame, and the fiber filaments are arranged on the tree-shaped parallel fine glass components.
[0010] Based on the structure of the above-mentioned efficient and simple lithium carbonate solution crystallization component, the tree-shaped side-by-side fine glass component includes a main rod and supporting rods. The supporting rods converge at the main rod, and the bottom of the supporting rod forms a support. The fiber filaments are attached along the length direction of each supporting rod and converge at the main rod.
[0011] Based on the above-mentioned structure of a high-efficiency and simple lithium carbonate solution crystallization assembly, the crystallization frame includes a main frame, a support cylinder, and a gripper; the support cylinder is located at the top of the main frame, and the gripper is located on the side wall of the support cylinder away from the main frame, with a rubber pad provided on the inner contact portion between the gripper and the support cylinder.
[0012] Based on the structure of the above-mentioned efficient and simple lithium carbonate solution crystallization component, the vent hole is a strip-shaped hole, the length of the strip-shaped hole is not less than the length of the gripper, so that the gripper can pass through the vent hole, and the width of the strip-shaped hole is not less than the size of the support cylinder.
[0013] This invention also discloses a highly efficient and simple method for crystallizing lithium carbonate solution; specifically, it includes the following steps:
[0014] Step 1: Lithium carbonate powder is processed through a solution preparation unit to obtain a saturated lithium carbonate solution;
[0015] Step 2: The saturated lithium carbonate solution is sent to the freezing unit to obtain a saturated lithium carbonate solution in the form of an ice-water mixture;
[0016] Step 3: The saturated lithium carbonate solution in the form of an ice-water mixture is fed into a filtration unit to remove excess undissolved lithium carbonate powder, resulting in a pretreated saturated lithium carbonate solution.
[0017] Step 4: The pretreated lithium carbonate saturated solution is fed into the crystallization unit by a peristaltic pump. After static crystallization by multiple fibers in the crystallization component, lithium carbonate crystal products are obtained.
[0018] In step one, specifically: 1.55g of lithium carbonate powder is mixed with 100ml of distilled water and stirred to obtain a saturated lithium carbonate solution;
[0019] In step two, specifically: the freezing process uses a freezer, and the freezer is kept at -15 degrees Celsius for 50 minutes.
[0020] In step three, the filtration process uses atmospheric pressure filtration; in step four, multiple hairs or carbon fibers are tightly attached and fixed to the glass piece so that the bottom of the fibers is submerged in the solution; the standing conditions are 25 degrees Celsius at room temperature.
[0021] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0022] 1. When using this component, first prepare a saturated lithium carbonate solution in a container, then place the prepared solution into a freezing component for freezing treatment to lower the solution temperature, which is beneficial for subsequent crystallization. Then, filter the frozen saturated solution to remove the insoluble lithium carbonate powder. Then, pump the liquid into the crystallization component for crystallization through fibers. Compared with traditional crystallization methods, this method can produce larger crystal particles. Finally, pump the waste liquid out of the crystallization component.
[0023] 2. In this solution, multiple tree-shaped parallel fine glass components are arranged along the length of the crystallization frame, and fiber filaments are attached to each glass tube. This allows for simultaneous batch crystallization, improving crystallization efficiency. The tree-shaped parallel fine glass components and some ends of the fiber filaments are exposed to the air, and crystallization is carried out through the fibers. Attached Figure Description
[0024] Figure 1 A schematic diagram of the overall structure of the invention;
[0025] Figure 2 This is a schematic diagram of the crystallization component in Example 2;
[0026] Figure 3 This is a flowchart of the experiment;
[0027] Figure 4 XRD analysis plot;
[0028] Figure 5 This is a schematic diagram of another set of experiments;
[0029] Figure 6 Electron microscope images of crystals; Voltage: 15kV; Magnification: (a) 150 / (b) 610 / (c) 300 / (d) 460 / (e);
[0030] Figure 7(I) and (II) are electron microscope images of the sample powder; (III) and (IV) are electron microscope images of the bottom of the cup; (V), (VI) and (VII) are electron microscope images of the cup-shaped object.
[0031] Figure 8 This is a schematic diagram of a vacuum drying experiment;
[0032] Figure 9 This is a schematic diagram of a fan acceleration experiment;
[0033] Figure 10 Microscopic images of crystal growth;
[0034] Figure 11 For illustration of other experiments;
[0035] Figure 12 The image shows the solid residue formed on the hair in solution 1 and lithium carbonate powder observed under a microscope.
[0036] The diagram shows the following components: 1. Freezing assembly; 2. Filtration assembly; 3. Crystallization assembly; 4. Drainage assembly; 5. Peristaltic pump; 21. Glass rod; 22. Filter paper; 23. Funnel; 31. Crystallizer; 32. Cover; 33. Glass carrier; 34. Fiber filament; 35. Crystallization frame; 36. Tree-like parallel fine glass components; 321. Vent hole; 351. Main frame; 352. Support cylinder; 353. Holder; 354. Rubber pad; 361. Main rod section; 362. Support rod. Detailed Implementation
[0037] All features disclosed in this specification, or all steps in all disclosed methods or processes, may be combined in any way, except for mutually exclusive features and / or steps.
[0038] Any feature disclosed in this specification (including any appended claims and abstract) may be replaced by other equivalent or similar features, unless specifically stated otherwise. That is, unless specifically stated otherwise, each feature is merely one example of a series of equivalent or similar features.
[0039] In the description of this invention, it should be understood that the terms "upper," "lower," "left," "right," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a predetermined orientation, or be constructed and operated in a predetermined orientation. Therefore, they should not be construed as limitations on this invention.
[0040] Furthermore, the terms "first," "second," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first," "second," etc., may explicitly or implicitly include one or more of that feature.
[0041] Example 1
[0042] like Figures 1-2 As shown, the present invention provides a technical solution:
[0043] A high-efficiency and simple lithium carbonate solution crystallization assembly 3 includes, but is not limited to, a freezing assembly 1, a filtration assembly 2, a crystallization assembly 3, and a drainage assembly 4; the freezing unit is used to freeze the prepared solution, the filtration assembly 2 is used to filter the frozen solution, the crystallization assembly 3 is used to crystallize the filtered solution, and the drainage assembly 4 is used to drain the waste liquid from the crystallization assembly 3; the crystallization assembly 3 is provided with fibers for crystallization, and the filtration assembly 2 and the drainage assembly 4 are connected to the crystallization assembly 3 through a pump.
[0044] Based on the above structure, when using this component, a saturated lithium carbonate solution is first prepared in a container. Then, the prepared solution is placed in the freezing component 1 for freezing treatment to lower the solution temperature, which is beneficial for subsequent crystallization. The frozen saturated solution is then filtered to remove insoluble lithium carbonate powder. The liquid is then pumped into the crystallization component 3 for crystallization via fibers. Compared with traditional crystallization methods, this method can produce larger crystal particles. Finally, the waste liquid in the crystallization component 3 is discharged by the pump.
[0045] As an example, the freezing component 1 can be a freezer, and the filtration component 2 can be a glass rod 21, filter paper 22, and funnel 23; the filter paper 22 is placed on the funnel 23, and the lithium carbonate solution is guided to the filter paper 22 for filtration through the glass rod 21; the filtration component 2 and the drainage component 4 are respectively connected to the crystallization component 3 through the peristaltic pump 5.
[0046] As an example, the crystallization component 3 may include a crystallizer 31, a cover 32, a glass carrier 33, and fiber filaments 34; the fiber filaments 34 are disposed on the glass carrier 33, the upper end of the crystallizer 31 is open, the cover 32 covers the crystallizer 31, and the cover 32 is provided with a vent hole 321.
[0047] Based on the above structure, during use, a glass carrier 33 with attached fiber filaments 34 is placed in the solution of the crystallizer 31, so that at least a portion of the length of the fiber filaments 34 is in contact with the lithium carbonate solution, allowing the fiber filaments 34 to crystallize rapidly.
[0048] Example 2
[0049] This embodiment provides another form of crystallization component 3, which may specifically include a crystallizer 31, a cover 32, a crystallization frame 35, tree-shaped parallel fine glass elements 36, and fiber filaments 34; the crystallizer 31 is provided with an opening at the upper end, the cover 32 is provided with a vent hole 321, the cover 32 covers the crystallizer 31, multiple tree-shaped parallel fine glass elements 36 are provided on the crystallization frame 35, and the fiber filaments 34 are provided on the tree-shaped parallel fine glass elements 36.
[0050] Based on the above structure, multiple tree-shaped parallel fine glass pieces 36 are arranged along the length of the crystallization frame 35 during use, and fiber filaments 34 are attached to each glass tube. This allows for simultaneous batch crystallization, improving crystallization efficiency. By exposing part of the ends of the tree-shaped parallel fine glass pieces 36 and fiber filaments 34 to the air, crystallization is carried out through the fibers.
[0051] As an example, the tree-like side-by-side thin glass element 36 may include a main rod 361 and supporting rods 362, the supporting rods 362 converging at the main rod 361, the bottom of the supporting rods 362 forming a support, and fiber filaments 34 adhering along the length direction of each supporting rod 362 and converging at the main rod 361.
[0052] Based on the above structure, each tree-shaped parallel fine glass element 36 has multiple supporting rods 362. On the one hand, the supporting rods 362 can support the tree-shaped parallel fine glass element 36, and on the other hand, they also provide a carrier for the fiber filaments 34 to facilitate crystallization.
[0053] As an example, the crystal frame 35 may include a main frame 351, a support cylinder 352 and a gripper 353; the support cylinder 352 is located at the top of the main frame 351, and the gripper 353 is located on the side wall of the support cylinder 352 away from the main frame 351. A rubber pad 354 may be provided on the inner contact portion between the gripper 353 and the support cylinder 352.
[0054] The vent 321 can be a strip-shaped hole, the length of which is not less than the length of the grip 353, so that the grip 353 can pass through the vent 321, and the width of which is not less than the size of the support cylinder 352.
[0055] Based on the above structure, during use, the gripper 353 can be rotated to a state parallel to the strip hole, passing through the strip hole, and then rotated to a state perpendicular to the strip hole, so that the gripper 353 contacts the upper part of the cover 32, suspending the main frame 351, which facilitates crystallization.
[0056] Example 3
[0057] This embodiment provides a highly efficient and simple method for crystallizing lithium carbonate solution; it specifically includes the following steps:
[0058] Step 1: Lithium carbonate powder is processed through a solution preparation unit to obtain a saturated lithium carbonate solution;
[0059] Step 2: The saturated lithium carbonate solution is sent to the freezing unit to obtain a saturated lithium carbonate solution in the form of an ice-water mixture;
[0060] Step 3: The saturated lithium carbonate solution in the form of an ice-water mixture is fed into a filtration unit to remove excess undissolved lithium carbonate powder, resulting in a pretreated saturated lithium carbonate solution.
[0061] Step 4: The pretreated lithium carbonate saturated solution is fed into the crystallization unit through peristaltic pump 5, and lithium carbonate crystals are obtained after static crystallization through multiple fibers in crystallization component 3.
[0062] In step one, specifically: 1.55g of lithium carbonate powder is mixed with 100ml of distilled water and stirred to obtain a saturated lithium carbonate solution;
[0063] In step two, specifically: the freezing process uses a freezer, and the freezer is kept at -15 degrees Celsius for 50 minutes;
[0064] In step three, the filtration process employs atmospheric pressure filtration.
[0065] In step four, multiple fibers (hair, carbon fiber) are tightly bonded and fixed to the glass piece, so that the bottom of the fibers is submerged in the solution; the standing conditions are 25 degrees Celsius at room temperature.
[0066] Example 4
[0067] This embodiment uses hair strands for crystallization:
[0068] Step 1: Use deionized water to mix with lithium carbonate powder, and after stirring and pretreatment, obtain a preliminary mixture;
[0069] Step 2: The preliminary mixture is sent to a freezer. After freezing, a completely dissolved lithium carbonate solution is obtained.
[0070] Step 3: The completely dissolved lithium carbonate solution is guided through a glass rod onto a funnel with filter paper. After filtration, a saturated lithium carbonate solution is obtained.
[0071] Step four: A saturated lithium carbonate solution is pumped into the crystallization device using a first peristaltic pump; a sufficiently long hair is attached to a glass slide to form a crystallization carrier; the crystallization carrier is then placed into the crystallization device, with the ends of the hair strands on the carrier immersed in the solution, resulting in a completed crystallization device; the crystallization device is placed in a suitable environment and allowed to air dry for a period of time, after which regularly shaped lithium carbonate crystals will form on the hair strands above the liquid surface; the solution in the completed crystallization device is pumped out using a second peristaltic pump, the crystallization carrier is removed, and the above operation is repeated to achieve repeated crystallization.
[0072] Example 5
[0073] This embodiment uses carbon fiber for crystallization:
[0074] Step 1: Use deionized water to mix with lithium carbonate powder, and after stirring and pretreatment, obtain a preliminary mixture;
[0075] Step 2: The preliminary mixture is sent to a freezer. After freezing, a completely dissolved lithium carbonate solution is obtained.
[0076] Step 3: The completely dissolved lithium carbonate solution is guided through a glass rod onto a funnel with filter paper. After filtration, a saturated lithium carbonate solution is obtained.
[0077] Step four: A saturated lithium carbonate solution is pumped into the crystallization device using a first peristaltic pump; a sufficiently long carbon fiber is attached to a glass slide to form a crystallization carrier; the crystallization carrier is then placed into the crystallization device, with the ends of the carbon fibers on the carrier immersed in the solution, resulting in a completed crystallization device; the crystallization device is placed in a suitable environment and allowed to air dry for a period of time, after which regularly shaped lithium carbonate crystals will form on the carbon fibers above the liquid surface; the solution in the completed crystallization device is pumped out using a second peristaltic pump, the completed crystallization carrier is removed, and the above operation is repeated to achieve repeated crystallization.
[0078] The inventors conducted experiments from multiple angles to demonstrate that by attaching fiber filaments to a glass component in a low-temperature saturated solution, large-volume crystallization can be achieved when the fiber filaments protrude from the liquid surface.
[0079] Experiment 1:
[0080] Laboratory equipment includes: beakers, stainless steel cups, plastic cups, a human hair, glass rods, laboratory-scale glass slides, hot melt adhesive (for fixing two glass slides), XRD instruments (for XRD measurements), carbon dioxide tanks, transparent adhesive tape, vacuum drying ovens, and constant temperature chambers. The structure is as follows: Figure 3 As shown;
[0081] Dissolve 1.55g of lithium carbonate powder in 100ml of distilled water at room temperature (22℃), stir thoroughly, and then refrigerate at 5℃ for 40-50 minutes. Remove the solution and stir again until homogeneous. Filter the solution. After filtration, place a strand of hair along the wall of a glass, ensuring one-third of the hair is submerged in the solution. Let it stand for one day. Crystals will precipitate around the hair, and over time, they will appear extensively around the hair. After several months of natural evaporation, crystals will appear on the bottom and walls of the container.
[0082] X-ray diffraction analysis (XRD, Rigaku Corporation D / max-RB) is used to characterize the crystalline morphology of products. Diffraction peaks diffuse, with most of the energy absorbed by the sample using a copper Kα radiation testing device. The horizontal axis in the figure represents twice the incident angle of the X-rays; the sample was scanned from 5° to 80° at a scan rate of 8° / min; the results are shown below. Figure 4 As shown in the figure, the peak values all appear between θ = 15° and 16.5°; the vertical coordinate of the horizontal plane is shifted upward by 8000 units, and the vertical coordinate of the vertical plane is shifted upward by 16000 units; the peak value of the vertical plane is 10000a.u. to 11000a.u.; and the peak values of the horizontal plane and the curved surface are 7500a.u. to 8000a.u.
[0083] There are two ways to place a hair in a solution: one is to suspend it in the solution without contacting any container surface; the other is to let the hair adhere to the wall of the container, such as... Figure 5 As shown; the experimental results indicate that crystals formed on hair strands attached to the container wall, while suspended hair strands showed no phenomenon. Through repeated experiments, it was observed that crystals formed around the hair strands, but always began to appear at a certain height above the liquid surface, rather than directly from the surface. The crystals formed on the hair strands exhibited a snowflake-like appearance, were regularly shaped, and had a relatively large area. Figure 6 and Figure 7 As shown, based on the electron microscope image, we can accurately measure that the diameter of the crystals prepared in the laboratory is between 500 μm and 1000 μm; while the diameter of the sample powder is only 10 μm to 15 μm; obviously, the volume changes by 50 to 100 times from powder to crystal.
[0084] The difference between the nucleation rate and growth rate of a crystal directly affects the final crystal morphology. If the nucleation rate is greater than the growth rate, more small crystals will be produced, potentially leading to crystal particle aggregation; conversely, larger crystals may be formed. Crystallization under vacuum conditions may accelerate the formation of a supersaturated solution, thus affecting the nucleation rate and ultimately the crystal morphology. Figure 8As shown in the control experiment, a prepared solution I (1.55g / 100ml) was placed in a vacuum drying oven under a vacuum environment (vacuum degree of 0.07MPa); another identical solution II (1.55g / 100ml) was placed outdoors. The results showed that at a temperature of 24℃~26℃ and a humidity of 45%~50%, after 24 hours, a small amount of crystals appeared on the glass plate of solution I, but the volume was very small and only trace. In contrast, the outdoor solution produced larger crystals that precipitated from a hair's breadth, and the mass was greater. Another identical solution III was prepared and placed in a vacuum drying oven, where a vacuum was first evacuated (vacuum degree of 0.07MPa). The vacuum level was 0.07 MPa. Then, CO2 gas at 25°C and 0.07 MPa was introduced to make the air pressure inside and outside the vacuum drying oven the same. After 24 hours, the vacuum level rose from 0 MPa to 0.01 MPa. However, no crystals precipitated on the glass plate of solution III. After standing for a month, the liquid levels of solutions I and III did not drop. Solution I had white strip-shaped lithium carbonate at the bottom, while solution III was colorless and had a pungent odor. The two solutions were taken out and placed outdoors. After standing for a day, crystals precipitated in both solutions. The crystals in solution I were smaller, and the crystals in solution III were larger.
[0085] like Figure 9 As shown, the sample was placed in a constant temperature chamber, and the temperature was changed by altering the ambient temperature around the beaker. A fan was then placed directly opposite the beaker, and its speed was adjusted to change the temperature. Two samples were compared (one placed in a room with slower airflow and higher temperature, and the other in a constant temperature chamber with faster airflow and lower temperature). After 24 hours, the sample with slower airflow and higher temperature grew more crystals, but smaller in size; the sample with faster airflow and lower temperature grew fewer crystals, but larger in size.
[0086] like Figure 10 The image shown is a microscopic view of crystals (left: low speed, high temperature; right: high speed, low temperature):
[0087] This plan also includes the following: Figure 11 The experiment shown demonstrates that large-area crystals with regular, snowflake-like shapes can form on both planar and curved surfaces. The experiment also indicates that crystals grow around the thickness of a human hair, regardless of whether the surface is vertical or horizontal. Therefore, the crystallization plane has virtually no effect on lithium carbonate crystallization.
[0088] In this study, we found that the crystallization of lithium carbonate is mainly influenced by the carrier, temperature, and container; glass containers produced the best crystallization results, followed by plastic cups, while stainless steel cups could not crystallize with a hair. At lower temperatures, crystal growth was slow but the crystals were larger. The growth surface also played a role; crystals grown on curved surfaces had a larger spread, while those grown on vertical planes had a smaller spread and more concentrated growth. Horizontal growth was the most difficult, resulting in smaller yields each time. (The volume comparison among the three can be observed using electron microscopy.) Furthermore, experiments showed that the solubility of lithium carbonate powder is greater in a pure carbon dioxide environment than at room temperature. In a pure carbon dioxide environment, 1.55g of powder completely dissolved in 100ml of distilled water (at normal room temperature, it would not dissolve completely and would leave a lot of powder residue at the bottom of the container), and the solution was clear and free of impurities, with a pungent odor. Although no crystallization occurred in a pure carbon dioxide environment, the volume of crystals obtained by placing the sample outdoors was significantly larger than that obtained by placing it outdoors directly. The experiment also found that crystals formed after vacuum settling and then placing the sample outdoors... The volume of the crystals produced is much smaller than that of the carbon dioxide environment and the volume of crystallization at normal room temperature. Directly introducing carbon dioxide gas will accelerate the dissolution of the solid. When too much solid powder is added and then placed outdoors, crystals will appear on the liquid surface and inside the liquid, not just on the walls and hair strands. Furthermore, when hair strands are placed without contact with the container walls, they will not play a role in crystallization. Only when the hair strands are in close contact with the walls will they play a role in crystallization. The diameter of the original sample powder is approximately 10μm to 15μm, while the diameter of the generated crystals is approximately 500μm to 1000μm. It can be seen that the volume change is quite significant.
[0089] Lithium carbonate crystallization experiment:
[0090] I. Apparatus: iron stand, refrigerator (-9 degrees Celsius), electronic balance, lithium carbonate powder, beaker, glass rod, filter paper, hair.
[0091] II. Steps:
[0092] 1. Weigh 1.55g of lithium carbonate powder using an electronic balance;
[0093] 2. Pour 100ml of distilled water into a beaker to prepare a lithium carbonate solution of 0.0155g / ml;
[0094] 3. Prepare three identical lithium carbonate solutions and name them solutions 1, 2, and 3 respectively;
[0095] 4. After freezing solution 1 directly in the refrigerator for 5 hours, take it out and observe whether it freezes. Then, slowly warm it up at room temperature.
[0096] Solutions 2 and 3 were frozen under the same conditions for 42 minutes and then removed.
[0097] After removing solutions 2 and 3, place solution 2 directly at room temperature (25 degrees Celsius) to air dry naturally.
[0098] After removing solution 3, filter the solution, freeze it again for 1.5 hours, and then let it air dry at room temperature.
[0099] 5. Place a hair into each of the three beakers of solution, with the hair adhering to the beaker wall. Let them stand for two days and then observe the phenomena.
[0100] III. Observation of Phenomena:
[0101] 1. Observe solution 1. After freezing for five hours, solution 1 was found to have frozen. After standing for two days, it thawed, the solvent decreased, and a white solid precipitated at the bottom of the beaker. The solid was relatively dense.
[0102] 2. Observe solution 2. After standing, it was found that the solvent decreased and white solid precipitated on both the beaker wall and the bottom of the beaker. The surface of the white solid at the bottom of the beaker was smooth, and the solid formed a ring on the beaker wall, which was shaped like a small snowflake (after shaking the solution, the ring fell off and sank to the bottom of the beaker). A long piece of white solid was found on the hair. After removing it with the hand along the hair, the long piece of solid broke into two pieces after being gently crushed by hand.
[0103] 3. Observe solution 3. When it was taken out of the refrigerator, it was found that it had formed an ice-water mixture. After standing, it was found that the solvent had decreased and no solid had precipitated, but white snowflake-like solids appeared on the hair.
[0104] 4. Place the three solutions together at room temperature for several days and observe again. Large, discolored, snowflake-like solids appeared in solution 1, while the snowflake-like solids in solutions 2 and 3 became significantly larger. Large, discolored, snowflake-like solids also appeared in solution 1.
[0105] IV. Controlled Experiment
[0106] 1. Steps:
[0107] Prepare two identical 0.0155 g / ml lithium carbonate solutions, freeze and filter them, and freeze them again for 35 minutes. In one solution, place a hair vertically into the center of the beaker and label it solution 5; in the other solution, place two hairs against the beaker wall and label it solution 4.
[0108] Prepare 300ml of lithium carbonate solution with a concentration of 0.0155g / ml, and label it solution 6. After freezing and filtering, put solution 5 back into the freezer for 1.5h. After taking it out, let it air dry at room temperature and observe the phenomenon.
[0109] Prepare two 300ml beakers of lithium carbonate solution with a concentration of 0.0155g / ml, labeled as solution 7 and solution 8. After freezing and filtration, remove the beakers and place a hair against the wall of each beaker. Allow the beakers to air dry at room temperature and observe the phenomena.
[0110] Prepare two 100ml lithium carbonate solutions with a concentration of 0.0155g / ml. After freezing and filtering, place a hair in each solution and press it tightly against the wall of the cup. Let one cup air dry at room temperature and record it as solution 10. Place the other cup in a vacuum desiccator, evacuate the device to a vacuum state, and let it air dry naturally and record it as solution 9.
[0111] Next, carbon dioxide was passed through the vacuum dryer containing solution 9, and a cup of distilled water was placed in the device to allow it to air dry naturally. After standing for two days, the distilled water was removed and allowed to air dry naturally.
[0112] Prepare two 100ml solutions containing 4.65g of lithium carbonate. Place a hair in each solution, pressing it tightly against the wall of the cup. Let one solution air dry at room temperature and label it Solution 12. Let the other solution air dry under vacuum and label it Solution 13.
[0113] Prepare 100ml of 0.0155g / ml lithium carbonate solution, denoted as solution 11. After freezing and filtration, continuously apply 12V to solution 11 for 10 minutes, then place a hair close to the cup wall and let it air dry at room temperature.
[0114] Solution 8 was continuously energized at 12V and then allowed to air dry at room temperature.
[0115] After freezing 67g of the solution containing impurities, it was continuously powered on at 6V2A and then allowed to air dry at room temperature. Hair that had already formed white snowflake-like solids was then placed into the solution.
[0116] The solution containing impurities was continuously electrified at 0.3V, then allowed to air dry at room temperature. A hair that had already developed a white solid was placed in the solution, and the mixture was left to stand for one day before being observed. Next, sufficient carbon dioxide was bubbled into the solution, and the mixture was left to stand for one day before being observed again.
[0117] Heat the solution containing impurities with an alcohol lamp, let it stand for a day, and then observe the phenomenon.
[0118] 2. Observe the phenomenon:
[0119] Neither solution reached the state of an ice-water mixture. No solid precipitated in solution 4, while white snowflake-like solids appeared on both hairs in solution 5. Compared with the solid obtained from solution 3, the snowflakes in solution 5 were smaller, and no solid precipitated at the bottom of the cup.
[0120] After solution 4 was left to stand at room temperature for several days (September 28th / October 6th), the solids on the two hairs were found to have significantly increased in size; in solutions 5 and 6, as the solvent decreased, long, truncated white solids appeared on the hairs, and they were almost the same size.
[0121] The solvent in solutions 7 and 8 decreased, and white snowflake-like solids appeared on the hair, with almost the same size.
[0122] After standing for 7 days, white snowflake-like solids appeared on the hair and the walls of the cup in solution 10, and the solvent decreased, while solution 9 showed no obvious phenomenon. After standing for a second time, solution 9 still showed no obvious change.
[0123] After standing for three days, the phenomenon was observed. It was found that the solvent in both solutions was almost unchanged, and white, long, truncated solids appeared on the hair.
[0124] After standing for one day, solution 11 was observed to show a significant reduction in solvent, and a large number of white fan-shaped solids and a small number of snowflake-shaped white solids appeared on the hair. The solids appeared at a significantly faster rate than in the un-electrified solution.
[0125] After standing, solution 8 was observed to show a significant decrease in solvent, the appearance of a ring-shaped white solid on the beaker wall, and the addition of white snowflake-like solids to the hair. The rate at which the solids appeared was significantly faster than in the un-electrified solution.
[0126] During the process of passing electricity through a solution containing impurities, white granular solids precipitate on the anode. After detaching from the solution, they turn green. After air drying at room temperature, the solution and the precipitated granular solids turn reddish-brown. A large amount of reddish-brown solids and black solids precipitate in the solution. The snowflake-like solids on the hair do not change significantly.
[0127] After standing for two periods, no obvious changes were observed in the impurity solution;
[0128] V. Microscopic observation
[0129] 1. The solid that formed on the hair in solution 1 was observed under a microscope (microscope magnification 100x) along with lithium carbonate powder. It was found that the solid was significantly larger than the lithium carbonate powder. Figure 12 As shown.
[0130] Airflow velocity comparison experiment:
[0131] Temperature: 23-27°C; Standing time: 48 hours;
[0132] After 48 hours of standing in an environment with a vacuum degree of 0.03 (0.07 complete vacuum), the vacuum degree of 1.55g / 100ml solution decreased by 0.06, no crystals appeared on the hair fibers, and the solid at the bottom of the container showed a wavy and porous appearance.
[0133] After 48 hours of standing in an open environment, a 1.55g / 100ml solution 1 showed obvious white crystals on the hair fibers, while the solid at the bottom of the container showed no obvious change.
[0134] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A highly efficient and simple method for crystallizing lithium carbonate solution, characterized in that: The invention includes a highly efficient and simple lithium carbonate solution crystallization assembly, comprising a freezing unit, a filtration unit, a crystallization unit, and a draining unit; the freezing unit is used to freeze the prepared solution, the filtration unit is used to filter the frozen solution, the crystallization unit is used to crystallize the filtered solution, and the draining unit is used to drain the waste liquid from the crystallization unit. The crystallization unit is equipped with fibers for crystallization, and the filtration assembly and drainage assembly are connected to the crystallization unit via a pump. The crystallization unit includes a crystallizer, a cover, a crystallization frame, tree-shaped parallel fine glass components, and fiber filaments; the crystallizer has an opening at the top, the cover has a vent hole, the cover is placed on the crystallizer, multiple tree-shaped parallel fine glass components are arranged on the crystallization frame, and the fiber filaments are arranged on the tree-shaped parallel fine glass components. The tree-shaped parallel thin glass component includes a main rod and supporting thin rods. The supporting thin rods converge at the main rod and form a support at the bottom of the supporting thin rod. The fiber filaments are attached along the length of each supporting thin rod and converge at the main rod. The crystallization frame includes a main frame, a support cylinder, and a gripper; the support cylinder is located at the top of the main frame, and the gripper is located on the side wall of the support cylinder away from the main frame, with a rubber pad provided on the inner contact part between the gripper and the support cylinder. The vent hole is a strip-shaped hole, the length of which is not less than the length of the grip, so that the grip can pass through the vent hole, and the width of which is not less than the size of the support cylinder; By rotating the grip to a position parallel to the slot and then rotating it to a position perpendicular to the slot, the grip contacts the upper part of the cover, suspending the main frame in the air. The method specifically includes the following steps: Step 1: Lithium carbonate powder is processed through a solution preparation unit to obtain a saturated lithium carbonate solution; Step 2: The saturated lithium carbonate solution is sent to the freezing unit to obtain a saturated lithium carbonate solution in the form of an ice-water mixture; In step two, specifically: the freezing process uses a freezer, and the freezer is set at -15 degrees Celsius for 50 minutes; Step 3: The saturated lithium carbonate solution in the form of an ice-water mixture is fed into a filtration unit to remove excess undissolved lithium carbonate powder, resulting in a pretreated saturated lithium carbonate solution. In step three, the filtration process uses atmospheric pressure filtration; in step four, multiple hairs or carbon fibers are tightly attached and fixed to the glass piece so that the bottom of the fibers is submerged in the solution; the settling condition is room temperature at 25 degrees Celsius. Step 4: The pretreated lithium carbonate saturated solution is fed into the crystallization unit by a peristaltic pump. After static crystallization by multiple fibers in the crystallization unit, lithium carbonate crystal products are obtained.
2. The efficient and simple lithium carbonate solution crystallization method as described in claim 1, characterized in that: In step one, specifically, 1.55g of lithium carbonate powder is mixed with 100ml of distilled water and stirred to obtain a saturated lithium carbonate solution.
3. The efficient and simple lithium carbonate solution crystallization method as described in claim 1, characterized in that: The freezing unit is a freezer, and the filtration assembly consists of a glass rod, filter paper, and a funnel. The filter paper is placed on the funnel, and the lithium carbonate solution is guided onto the filter paper for filtration through the glass rod. The filtration assembly and the drainage assembly are respectively connected to the crystallization unit through peristaltic pumps.
Citation Information
Patent Citations
Method and system for rapid extraction of lithium carbonate from salt lake water
CN103318928A